FORMULASI GEL HAND SANITIZER EKSTRAK DAUN PALIASA (Kleinhovia hospita Linn) DENGAN GELLING AGENT HPMC - Yetri Elisya; Wardiyah Wardiyah; Junaedi Junaedi; Farah Hamidah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Gel hand sanitizer is a novel product formula that can be utilized as a cost-effective and portable replacement for hand washing soap. One of the plants whose leaves can be used as a central component of hand sanitizer gel is the Paliasa plant (Kleinhovia hospita Linn). Staphylococcus and Escherichia coli resist the antimicrobial effects of alkaloids, tannins, and saponins. To create the hand sanitizer gel, three different concentrations of the HPMC gelling ingredient were used: 1%, 2%, and 3%. Variations in the amount of HPMC used in each formulation impact the gel's characteristics, particularly its viscosity, spreadability, and adherence. Following the cycle test, the three formulations' viscosity decreased, but their pH, spreadability, and stickiness increased. There was no significant difference between the stability test on day 0 and day 12 for pH, viscosity, spreadability, and gel adhesion, according to testing utilizing the paired sample T-test. > 0.05.